Efektivitas Program Bimbingan Belajar Bahasa Inggris untuk Siswa SD IT Imam Syafi’i Pekanbaru - Oktadela, Resy; Elida, Yusti; Hadiyanti, Putri Octa; Herman, Herman; Yuliani, Sri (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This tutoring program was organized to provide assistance in learning English for elementary school children, as an effort to improve their ability to communicate in English. This community service activity was carried out at SD IT Imam Syafi’i in Pekanbaru. The program involved 25 elementary school students from grades 4 to 6 at the school. The tutoring sessions were conducted over a period of two months. The methods used in the implementation of this program included socialization, training, and mentoring.The results of the activity showed that the children were very enthusiastic and interested in the program. Before participating in the program, the initial test results showed that only 1 out of 25 students passed, with an average score of 55. This indicated the need for additional guidance in English. After participating in the tutoring program, the final test results showed a significant improvement: all participants successfully passed. According to the data, 9 children scored between 60–69, while 13 children scored between 70–79, with the overall average score increasing to 70.Thus, this English tutoring program has proven to significantly improve the learning abilities of elementary school children.